2021
DOI: 10.1037/per0000463
|View full text |Cite
|
Sign up to set email alerts
|

Antisocial personality traits transcend species.

Abstract: Antisocial personality is generally used to describe people who treat other people with callous disregard and disrespect. Although animal cruelty is diagnostic of conduct disorder, a precursor of antisocial personality in children, it is unclear whether the term antisocial also encompasses disregard and disrespect toward non-human animals among adults. In this study we examined associations between three anti-animal attitudes and behaviors-speciesism, hunting/fishing, and lack of sympathy for animal rights-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 66 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…All three studies that examined RWA found that omnivorism was associated with significantly greater RWA compared to vegetarianism (Allen et al, 2000;Ruby et al, 2013;Veser et al, 2015). All five studies that measured SDO came to a consistent conclusion that omnivorism was associated with a significantly greater SDO than vegetarianism (Allen et al, 2000;Bilewicz et al, 2011;Piazza et al, 2015;Veser et al, 2015;Hopwood and Bleidorn, 2020). In line with these findings, the study conducted by Veser et al (2015) indicated a significantly higher tendency to be prejudiced among omnivores than among vegetarians.…”
Section: Personalitymentioning
confidence: 64%
See 4 more Smart Citations
“…All three studies that examined RWA found that omnivorism was associated with significantly greater RWA compared to vegetarianism (Allen et al, 2000;Ruby et al, 2013;Veser et al, 2015). All five studies that measured SDO came to a consistent conclusion that omnivorism was associated with a significantly greater SDO than vegetarianism (Allen et al, 2000;Bilewicz et al, 2011;Piazza et al, 2015;Veser et al, 2015;Hopwood and Bleidorn, 2020). In line with these findings, the study conducted by Veser et al (2015) indicated a significantly higher tendency to be prejudiced among omnivores than among vegetarians.…”
Section: Personalitymentioning
confidence: 64%
“…Three studies collected data about right-wing authoritarianism (RWA), namely, Allen et al (2000) and Ruby et al (2013). These three studies used the "Right-Wing Authoritarianism Scale" (Altemeyer, 1981), which Veser et al (2015) collected via Five studies (Allen et al, 2000;Bilewicz et al, 2011;Piazza et al, 2015;Veser et al, 2015;Hopwood and Bleidorn, 2020, short form) investigated social dominance orientation (SDO) using the "Social Dominance Orientation Scale" (Pratto et al, 1994). Furthermore, studies assessed the tendency to be prejudiced through the "Motivation for Prejudice-Free Behavior Scale" (Banse and Gawronski, 2003;Veser et al, 2015), misanthropy (Rothgerber, 2015b), social desirability (Sims, 1978), self-esteem (Nezlek et al, 2018), self-efficacy (Cruwys et al, 2020), and self-control via the "Brief Self-Control Scale" (Tangney et al, 2004;Cruwys et al, 2020), and strictness (Rosenfeld and Burrow, 2018), absolutism, and guilt over violating one's diet (Rothgerber, 2015a).…”
Section: Personalitymentioning
confidence: 99%
See 3 more Smart Citations